2015
DOI: 10.1007/s00590-015-1659-5
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment in spine Paget’s disease: a systematic review

Abstract: Paget's disease of bone (PDB) is a disease characterized by a disorder in the bone metabolism. The spine is the second region affected after the pelvis. Surgical treatment is reserved for cases refractory to medical treatment. We performed a systematic review of patients with Paget disease of bone affecting the spine, treated surgically in the last 30 years. The main objective of the review is to find out indications for surgery, outcomes of these patients and also the standard perioperative management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…Blood loss was estimated as 300ml (range 100-600ml) but the authors found no difference between blood loss in patients who had or had not received pre-operative treatment with etidronate (278ml vs. 315ml, p=0.32) (105). A systematic review conducted by Jorge-Mora and colleagues reviewed the effects of anti-Pagetic therapy on blood loss and other outcomes after elective spinal surgery in 17 case reports (106). The most common indications for surgery were spinal cord compression (n=8), spinal stenosis (n=6) and back pain (n=3).…”
Section: Effects Of Drug Treatment In Paget’s Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Blood loss was estimated as 300ml (range 100-600ml) but the authors found no difference between blood loss in patients who had or had not received pre-operative treatment with etidronate (278ml vs. 315ml, p=0.32) (105). A systematic review conducted by Jorge-Mora and colleagues reviewed the effects of anti-Pagetic therapy on blood loss and other outcomes after elective spinal surgery in 17 case reports (106). The most common indications for surgery were spinal cord compression (n=8), spinal stenosis (n=6) and back pain (n=3).…”
Section: Effects Of Drug Treatment In Paget’s Diseasementioning
confidence: 99%
“…Jorge-Mora and colleagues (106) conducted a systematic review of patients undergoing surgical treatment of the spine in Paget’s disease and identified 17 studies all of which described single case reports. The commonest indication for surgery was spinal cord compression (n=8) spinal stenosis (n=6) and low back pain.…”
Section: Effects Of Non-pharmacological Treatments In Paget’s Diseasementioning
confidence: 99%
“…Patients should be screened by a cardiologist, as the often hypovascularized bone in Paget’s disease can lead to increased cardiac output with impaired cardiac function, 2 , 17 , 36 which might be even aggravated due to the frequently observed excessive blood loss during surgery in patients suffering from Paget’s Disease. 15 , 16 To reduce the risk of excessive blood loss during surgery, some authors advocated the use of anti-Pagetic treatment such as bisphosphonates and calcitonin before elective surgery, 14 , 15 , 16 , 17 , 35 , 41 although there is currently insufficient evidence to support this recommendation. 39 In any way, surgeons should be prepared to react to increased blood loss with the use of a cell saver system and blood products readily available on standby.…”
Section: Discussionmentioning
confidence: 99%
“…Sie merkten auch an, dass die Vorbehandlung den intraoperativen Blutverlust deutlich reduzierte und dass der geschätzte Blutverlust bei Patienten mit aktiver Paget-Krankheit höher war. Aber es wurden keine Informationen zum Blutverlust und zur Krankheitsaktivität gegeben 16 17 18 19 20 .…”
Section: Blutverlust Bei Elektiven Orthopädischen Eingriffenunclassified